Social movements and Europeanization - Della Porta, Donatella, 1956-; Caiani, Manuela (Oxford : Oxford University Press, 2009)
'Social Movements and Europeanization' addresses the relationship between social movements and Europe, locating contemporary social movements in a broader scenario of political conflicts around European integration.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social movements -- Europe; Europe -- Economic integration -- Public opinion; Europe -- Economic integration -- Social aspects